An Analysis Bankruptcy Prediction on Stock Price Through Earnings Per Share at PT. Bank Mandiri (Persero) Tbk. - Fahmi Mauludin; Nor Norisanti; Erry Sunarya (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2020)
This study aims to measure the effect of bankruptcy predictions on the stock price and earning per share as an intervening variable. The object used is PT. Bank Mandiri (Persero) Tbk. and data used is secondary data containing the company's monthly financial statements from 2016-2019 and stock data from Indonesia Stock Exchange. This study uses path analysis with SPSS program. The results of the study show that bankruptcy predictions have a direct and significant effect on stock prices, and bankruptcy predictions have an indirect and significant effect on stock prices through earnings per share.